2006
DOI: 10.1002/jez.a.265
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and development of testis in the oviparous lizard,Calotes versicolor (Daud.)

Abstract: The differentiation and development of the testis in the lizard Calotes versicolor was studied histologically and histoenzymatically from the day of oviposition (stage 27) to 2 months after hatching. The study reveals the appearance of the gonadal component as a genital ridge at stage 27. The first sign of testis differentiation is observed at stage 33, which displays a well-developed medulla consisting of seminiferous cords comprising Pre-Sertoli cells. The sex differentiation of the embryonic gonads occurs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 25 publications
4
26
0
Order By: Relevance
“…In the studied population females oviposit eggs containing embryos at Dufaure and Hubert's (1961) stages 31-33 (Braña et al 1991, and additional unpublished data), at which time endogenous production of steroid hormones is unlikely. Detailed studies in the lizard Calotes versicolor indicated that gonadal diVerentiation begins at stage 34 and there was no appreciable steroidogenesis until stage 36 in both male and female embryos (Doddamani 2005(Doddamani , 2006. Similar results were reported in the lizard Sceloporus undulatus (Austin 1988) and in green anoles (Anolis carolinensis; Lovern and Wade 2003b).…”
Section: Discussionsupporting
confidence: 81%
“…In the studied population females oviposit eggs containing embryos at Dufaure and Hubert's (1961) stages 31-33 (Braña et al 1991, and additional unpublished data), at which time endogenous production of steroid hormones is unlikely. Detailed studies in the lizard Calotes versicolor indicated that gonadal diVerentiation begins at stage 34 and there was no appreciable steroidogenesis until stage 36 in both male and female embryos (Doddamani 2005(Doddamani , 2006. Similar results were reported in the lizard Sceloporus undulatus (Austin 1988) and in green anoles (Anolis carolinensis; Lovern and Wade 2003b).…”
Section: Discussionsupporting
confidence: 81%
“…Hence, steroidogenic potency of adrenocortical cells prior to gonad may be considered. This further supports earlier work from our laboratory (Doddamani, 1994(Doddamani, , 2000(Doddamani, , 2006.…”
Section: Immunohistochemistry (Ihc)supporting
confidence: 90%
“…The endogenous production of estrogen may act in a paracrine fashion to induce neighboring cells into ovarian differentiation pathway to direct ovarian differentiation at FPT. The enzyme immunohistochemistry of the developing gonad in C. versicolor has already revealed that morphological differentiation of gonad precedes the onset of steroidogenesis (Doddamani, 1994(Doddamani, , 2000(Doddamani, , 2006. The immunohistochemistry is more reliable and sensitive than enzyme histochemistry and the results of the current study suggest that the synthesis of estrogen in the developing gonad coincides with sexual differentiation of the gonad.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 49%
“…Another group of cells differentiates into peritubular myoid cells, which envelop the testis cords to form seminiferous tubules [Morrish and Sinclair, 2002]. A third cell type, the interstitial cells of Leydig, differentiates between the testis cords and seminiferous tubules [Doddamani, 2006]. The final distinguishing feature of testis morphogenesis is formation of the male-specific vasculature [Morrish and Sinclair, 2002].…”
mentioning
confidence: 99%